Effect of heterogeneity on radionuclide retardation in the alluvial aquifer near Yucca Mountain, Nevada - Painter, S (Ground water, 2001)
The U.S. Department of Energy is currently studying Yucca Mountain, Nevada, as a potential site for a geological high-level waste repository. In the current conceptual models of radionuclide transport at Yucca Mountain, part of the transport path to pumping locations would be through an alluvial aquifer. Interactions with minerals in the alluvium are expected to retard the downstream migration of radionuclides, thereby delaying arrival times and reducing ground water concentrations. We evaluate the effectiveness of the alluvial aquifer as a transport barrier using the stochastic Lagrangian framework. A transport model is developed to account for physical and chemical heterogeneities and rate-limited mass transfer between mobile and immobile zones. The latter process is caused by small-scale heterogeneity and is thought to control the macroscopic-scale retardation in some field experiments. A geostatistical model for the spatially varying sorption parameters is developed from a site-specific database created from hydrochemical measurements and a calibrated modeling approach (Turner and Pabalan 1999). Transport of neptunium is considered as an example. The results are sensitive to the rate of transfer between mobile and immobile zones, and to spatial variability in the hydraulic conductivity. Chemical heterogeneity has only a small effect, as does correlation between hydraulic conductivity and the neptunium distribution coefficient. These results illustrate how general sensitivities can be explored with modest effort within the Lagrangian framework. Such studies complement and guide the application of more detailed numerical simulations